Estimation of environmental impacts of roads through life cycle assessment: A critical review and future directions - Jiang, R.; Wu, Peng (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Motivated by the lack of a systematic analysis of the use of life cycle assessment (LCA) to estimate the environmental impacts of roads, this study conducts a critical review to examine the methods, common practices, limitations, and underlying reasons, so that future directions can be recommended. In this work, 94 papers that adopt LCA methods to assess the environmental impacts over the whole life cycle of roads were analyzed. The results demonstrate that the process-based LCA remains the most commonly adopted LCA method; however, the hybrid LCA has been gradually recognized. After examining the goal and scope definition, life cycle inventory, life cycle impact assessment, and life cycle interpretation of these studies, it was found that the current LCA applications in roads face limitations owing to the inconsistent and inappropriate selection of the functional unit, limited consideration of the maintenance and repair, use, and end-of-life phases, limited reporting of data sources, lack of standardized impact assessment procedures, and lack of sensitivity and uncertainty analyses. These limitations can be attributed to the lack of a standardized LCA procedure for roads. There is also a lack of LCA studies focusing on network-level analysis, which may restrict the use of LCA to assist policy making in road planning and management. In addition, the time effect is rarely considered to reflect the dynamic changes of environmental impacts over the project life cycle. Therefore, future directions are recommended accordingly. Improvements in these areas are expected to generate more reliable LCA results for informed decision making.